Eigensolutions and Thermodynamic Properties of Kratzer Plus Generalized Morse Potential - Isonguyo, Cecilia N.; Okon, Ituen B.; Antia, Akaninyene D.; Oyewumi, Kayode J.; Omugbe, Ekwevugbe; Onate, Clement A.; Joshua, Roseline U.; Udoh, Monday E.; Ituen, Eno E.; Araujo, Judith P. (Frontiers in Physics, 2022)
In this study, we apply the parametric Nikiforov-Uvarov method to obtain the bound state solution of Schrodinger wave equation in the presence of Kratzer plus generalized Morse potential (KPGM). The energy eigen equation and the corresponding normalised wave function were obtained in closed form. The resulting energy eigen equation were use to study partition function and other thermodynamic properties such as vibrational mean energy, vibrational specific heat capacity, vibrational mean free energy and vibrational entropy for the proposed potential as applied to lithium hydride diatomic molecule. The thermodynamic plots obtained were in excellent agreement to work of existing literatures. The wave function and probability density plots for the diatomic molecules were obtained through a well designed and implemented maple programme.